Probing multivalency in ligand–receptor-mediated adhesion of soft, biomimetic interfaces - Schmidt, Stephan; Wang, Hanqing; Pussak, Daniel; Mosca, Simone; Hartmann, Laura (Beilstein Journal of Organic Chemistry, 2015)
Many biological functions at cell level are mediated by the glycocalyx, a dense carbohydrate-presenting layer. In this layer specific interactions between carbohydrate ligands and protein receptors are formed to control cell–cell recognition, cell adhesion and related processes. The aim of this work is to shed light on the principles of complex formation between surface anchored carbohydrates and receptor surfaces by measuring the specific adhesion between surface bound mannose on a concanavalin A (ConA) layer via poly(ethylene glycol)-(PEG)-based soft colloidal probes (SCPs). Special emphasis is on the dependence of multivalent presentation and density of carbohydrate units on specific adhesion. Consequently, we first present a synthetic strategy that allows for controlled density variation of functional groups on the PEG scaffold using unsaturated carboxylic acids (crotonic acid, acrylic acid, methacrylic acid) as grafting units for mannose conjugation. We showed by a range of analytic techniques (ATR–FTIR, Raman microscopy, zeta potential and titration) that this synthetic strategy allows for straightforward variation in grafting density and grafting length enabling the controlled presentation of mannose units on the PEG network. Finally we determined the specific adhesion of PEG-network-conjugated mannose units on ConA surfaces as a function of density and grafting type. Remarkably, the results indicated the absence of a molecular-level enhancement of mannose/ConA interaction due to chelate- or subsite-binding. The results seem to support the fact that weak carbohydrate interactions at mechanically flexible interfaces hardly undergo multivalent binding but are simply mediated by the high number of ligand–receptor interactions.
Keywords: bio-interfaces; cell mimetic; glycocalyx; glycopolymer; molecular recognition; RICM; specific adhesion